Frontal face of the Shikhara - Temples of India Project Team (Jio Institute, 2024)
The frontal face of the shikhara (superstructure) reveals the placement of two half spires flanking the main spire. At the base of the spire, a surasenaka (pediment made of chaitya dormer) adorns the structure, while a sculpture depicts a simha (lion) pouncing upon an elephant, adding a touch of regal splendour to the architectural composition.